2008
DOI: 10.1080/13880200802055891
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Selected Natural Products on Neutral Endopeptidase Activity and β-Amyloid Production in SK-N-SH Cells

Abstract: Neutral endopeptidase (NEP) and angiotensin-converting enzyme (ACE) belong to the major Aβ-degrading enzymes. We currently demonstrate that apigenin, luteolin, and curcumin are able to enhance the activity of NEP and ACE. In this research, we examined the influence of these substances on the amount of endogenously produced and secreted Aβ of neuroblastoma cells. We found that treatment of the cells for 72 h with apigenin, luteolin, and curcumin decreases the endogenous Aβ1-42 level of SK-N-SH cells significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Previously, somatostatin, rolipram, luteolin, apigenin, and curcumin was reported showing the ability of increasing NEP activity using activity assay but there was no supporting data showing increase in NEP mRNA or protein levels 16 40 . Using activity assay alone could not exclude the possibility the substrate degradation coming from the action of other proteases.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previously, somatostatin, rolipram, luteolin, apigenin, and curcumin was reported showing the ability of increasing NEP activity using activity assay but there was no supporting data showing increase in NEP mRNA or protein levels 16 40 . Using activity assay alone could not exclude the possibility the substrate degradation coming from the action of other proteases.…”
Section: Discussionmentioning
confidence: 96%
“…Certain medicinal plants are thought to be effective in improving brain function, and secondary metabolites in plants have been extensively examined as possible AD therapeutic reagents. Ayoub and Melzig found that apigenin, luteolin, and curcumin increased both ACE and NEP activity and rolipram increased only NEP activity in human SK-N-SH neuroblastoma cells 16 . Eisele et al .…”
mentioning
confidence: 99%
“…For instance, Saito et al [ 22 ] used a concentration of glutaryl-Ala-Ala-Phe-methoxy-2-naphthylamide (Sigma) of 500 μM and this peptide substrate could be digested by many other proteases [ 23 ]. SAAP-AMC (Suc-L-Ala-L-Ala-L-Phe-7-amido-3-methylcoumarin, Sigma) [ 25 , 26 ] was used to screen natural compounds that could increase NEP activity in the neuroblastoma SK-N-SH cells. The substrate concentration was 44 μM and a subsequent digestion step by aminopeptidase N was required.…”
Section: Resultsmentioning
confidence: 99%
“…Referring to the studies searching for agents that may up-regulate NEP gene expression; enhancing its activity and promoting its action (Borson, 1991), a variety of selective enhancers are pre-clinically developed involving drugs (glucocorticoids) (Borson and Gruenert, 1991), hormones (androgens (Yao et al, 2008) and estrogen (Xiao et al, 2009)) or natural products (Apigenin, Luteolin, and Curcumin, (-)-Epigallocatechin-3-gallate and Resveratrol) (Ayoub and Melzig, 2008;Chang et al, 2015;El-Sayed and Bayan, 2015).…”
Section: Potential Covid-19 Therapiesmentioning
confidence: 99%
“…Along with, Rolipram, an investigative PDE4i, has also been examined; suggesting that increasing the levels of intracellular cAMP was directly correlated with enhanced NEP activity, which in turn may prolong and potentiate the cAMP-mediated short-term anti-inflammatory mechanism (Graf et al, 1995;Ayoub and Melzig, 2008).…”
Section: Potential Covid-19 Therapiesmentioning
confidence: 99%